Guía de estimulación cognitiva para mejorar la atención y memoria en estudiantes de la carrera de comunicación de la Facultad de la Educación, el Arte y la Comunicación de la Universidad Nacional de Loja. Periodo académico 2024 – 2025 - Ordóñez Alvarado, Marena Beatriz (2025)
The general objective of this curricular integration work was to propose a cognitive stimulation guide for attention and memory in students of the communication career at the Faculty of Education, Art and Communication of the National University of Loja. Academic period 2024 - 2025. The methodology used corresponds to a qualitative-quantitative approach, descriptive and cross-sectional with a non-experimental design. We worked with the teachers of the first term of the career, to whom a survey was applied to find out the didactic and psychopedagogical strategies they use to stimulate attention and memory. The results show that 57% of teachers use group discussions as didactic and psychopedagogical strategies and 43% develop analytical, critical thinking and problem-solving activities that serve in their participation and in the construction of their own knowledge; however, 50% indicate that students would pay more attention if the activities were dynamic and entertaining. Therefore, it is concluded that teachers do use group and analytical strategies, but they are insufficient to motivate students; therefore, it is necessary to propose an alternative to stimulate the cognitive processes of attention and memory by designing a cognitive stimulation guide